The teaching about imprisonment of liberty as a form of punishment in the coordinate system of penitential criminopenology - Shidlovsky, Andrei V. (Journal of the Belarusian State University. Law, 2024)
Theoretical foundations of penitentiary criminopenology are being developed, which allows us to talk about classifying deprivation of liberty as a type of punishment as a penitentiary type of criminal liability. This direction creates the prerequisites for a comprehensive solution to the problem of saving penalisation, including penitentiary repression at all stages of its regulation (from the establishment of criminal law sanctions to full implementation in relation to a specific convict). The system of penitentiary criminology is revealed as an independent direction in the doctrine of punishment by deprivation of liberty, its subject and main parameters are determined. Certain aspects of the social, criminal-political, criminological and criminal-legal conditionality of the nature of differentiation and individualisation of criminal penitentiary repression are considered. The content of punishment in the form of imprisonment is analysed in terms of measuring the parameters of penitentiary criminology. On this basis, the content of the protective task of criminal law in the conditions of the development of the social state and modern society is clarified.
Keywords: imprisonment; penitentiary criminopenology; penitentiary type of criminal behaviour; punishment; differentiation and individualisation of penitentiary repression